Group-13 and group-15 doping of germanane - Cultrara, Nicholas D.; Arguilla, Maxx Q.; Jiang, Shishi; Sun, Chuanchuan; Scudder, Michael R.; Ross, R. Dominic; Goldberger, Joshua E. (Beilstein Journal of Nanotechnology, 2017)
Germanane, a hydrogen-terminated graphane analogue of germanium has generated interest as a potential 2D electronic material. However, the incorporation and retention of extrinsic dopant atoms in the lattice, to tune the electronic properties, remains a significant challenge. Here, we show that the group-13 element Ga and the group-15 element As, can be successfully doped into a precursor CaGe2 phase, and remain intact in the lattice after the topotactic deintercalation, using HCl, to form GeH. After deintercalation, a maximum of 1.1% As and 2.3% Ga can be substituted into the germanium lattice. Electronic transport properties of single flakes show that incorporation of dopants leads to a reduction of resistance of more than three orders of magnitude in H2O-containing atmosphere after As doping. After doping with Ga, the reduction is more than six orders of magnitude, but with significant hysteretic behavior, indicative of water-activation of dopants on the surface. Only Ga-doped germanane remains activated under vacuum, and also exhibits minimal hysteretic behavior while the sheet resistance is reduced by more than four orders of magnitude. These Ga- and As-doped germanane materials start to oxidize after one to four days in ambient atmosphere. Overall, this work demonstrates that extrinsic doping with Ga is a viable pathway towards accessing stable electronic behavior in graphane analogues of germanium.
Keywords: doping; electronic behavior; germanane; two-dimensional materials

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Katsnelson, M. I.; Grigorieva, I. V.; Dubonos, S. V.; Firsov, A. A. (Nature, 2005)

(untitled) - Garcia, J. C.; de Lima, D. B.; Assali, L. V. C.; Justo, J. F. (J. Phys. Chem. C, 2011)

(untitled) - Jiang, S.; Arguilla, M. Q.; Cultrara, N. D.; Goldberger, J. E. (Acc. Chem. Res., 2015)

(untitled) - Pulci, O.; Gori, P.; Marsili, M.; Garbuio, V.; Del Sole, R.; Bechstedt, F. (Europhys. Lett., 2012)

(untitled) - Vogg, G.; Brandt, M. S.; Stutzmann, M. (Adv. Mater., 2000)

(untitled) - Vogt, P.; De Padova, P.; Quaresima, C.; Avila, J.; Frantzeskakis, E.; Asensio, M. C.; Resta, A.; Ealet, B.; Le Lay, G. (Phys. Rev. Lett., 2012)

(untitled) - Wei, W.; Dai, Y.; Huang, B.; Jacob, T. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Bonaccorso, F.; Colombo, L.; Yu, G.; Stoller, M.; Tozzini, V.; Ferrari, A. C.; Ruoff, R. S.; Pellegrini, V. (Science, 2015)

(untitled) - De Padova, P.; Vogt, P.; Resta, A.; Avila, J.; Razado-Colambo, I.; Quaresima, C.; Ottaviani, C.; Olivieri, B.; Bruhn, T.; Hirahara, T.; Shirai, T.; Hasegawa, S.; et al. (Appl. Phys. Lett., 2013)

(untitled) - Zhang, R.-W.; Zhang, C.-W.; Ji, W.-X.; Li, S.-S.; Hu, S.-J.; Yan, S.-S.; Li, P.; Wang, P.-J.; Li, F. (New J. Phys., 2015)

(untitled) - Zhang, R.-w.; Zhang, C.-w.; Ji, W.-x.; Li, S.-s.; Yan, S.-s.; Hu, S.-j.; Li, P.; Wang, P.-j.; Li, F. (Sci. Rep., 2016)

(untitled) - Zhao, H.; Ji, W.-x.; Zhang, C.-w.; Li, P.; Zhang, S.-f.; Li, F.; Wang, P.-j.; Li, S.-s.; Yan, S.-s. (J. Mater. Chem. C, 2017)

(untitled) - Zhang, R.-w.; Ji, W.-x.; Zhang, C.-w.; Li, S.-s.; Li, P.; Wang, P.-j. (J. Mater. Chem. C, 2016)

(untitled) - Wang, Y.-p.; Ji, W.-x.; Zhang, C.-w.; Li, P.; Li, F.; Ren, M.-j.; Chen, X.-L.; Yuan, M.; Wang, P.-j. (Sci. Rep., 2016)

(untitled) - Radisavljevic, B.; Kis, A. (Nat. Mater., 2013)

(untitled) - Radisavljevic, B.; Radenovic, A.; Brivio, J.; Giacometti, V.; Kis, A. (Nat. Nanotechnol., 2011)

(untitled) - Wang, Q. H.; Kalantar-Zadeh, K.; Kis, A.; Coleman, J. N.; Strano, M. S. (Nat. Nanotechnol., 2012)

(untitled) - Mak, K. F.; Lee, C.; Hone, J.; Shan, J.; Heinz, T. F. (Phys. Rev. Lett., 2010)

(untitled) - Zhang, R. W.; Ji, W. X.; Zhang, C. W.; Li, P.; Wang, P. J. (arXiv, 2016)

(untitled) - Arguilla, M. Q.; Cultrara, N. D.; Baum, Z. J.; Jiang, S.; Ross, R. D.; Goldberger, J. E. (Inorg. Chem. Front., 2017)

(untitled) - Arguilla, M. Q.; Katoch, J.; Krymowski, K.; Cultrara, N. D.; Xu, J.; Xi, X.; Hanks, A.; Jiang, S.; Ross, R. D.; Koch, R. J.; Ulstrup, S.; Bostwick, A.; et al. (ACS Nano, 2016)

(untitled) - Geim, A. K.; Grigorieva, I. V. (Nature, 2013)

(untitled) - Dávila, M.; Xian, L.; Cahangirov, S.; Rubio, A.; Le Lay, G. (New J. Phys., 2014)

(untitled) - Butler, S. Z.; Hollen, S. M.; Cao, L.; Cui, Y.; Gupta, J. A.; Gutiérrez, H. R.; Heinz, T. F.; Hong, S. S.; Huang, J.; Ismach, A. F.; Johnston-Halperin, E.; Kuno, M.; et al. (ACS Nano, 2013)

(untitled) - Bianco, E.; Butler, S.; Jiang, S.; Restrepo, O. D.; Windl, W.; Goldberger, J. E. (ACS Nano, 2013)

(untitled) - Jiang, S.; Bianco, E.; Goldberger, J. E. (J. Mater. Chem. C, 2014)

(untitled) - Jiang, S.; Butler, S.; Bianco, E.; Restrepo, O. D.; Windl, W.; Goldberger, J. E. (Nat. Commun., 2014)

(untitled) - Jiang, S.; Krymowski, K.; Asel, T.; Arguilla, M. Q.; Cultrara, N. D.; Yanchenko, E.; Yang, X.; Brillson, L. J.; Windl, W.; Goldberger, J. E. (Chem. Mater., 2016)

(untitled) - Young, J. R.; Chitara, B.; Cultrara, N. D.; Arguilla, M. Q.; Jiang, S.; Fan, F.; Johnston-Halperin, E.; Goldberger, J. E. (J. Phys.: Condens. Matter, 2015)

(untitled) - Madhushankar, B. N.; Kaverzin, A.; Giousis, T.; Potsi, G.; Gournis, D.; Rudolf, P.; Blake, G. R.; van der Wal, C. H.; van Wees, B. J. (2D Mater., 2017)

(untitled) - Arguilla, M. Q.; Jiang, S.; Chitara, B.; Goldberger, J. E. (Chem. Mater., 2014)

(untitled) - Luo, X.; Zurek, E. (J. Phys. Chem. C, 2015)

(untitled) - Leonhardt, G.; Berndtsson, A.; Hedman, J.; Klasson, M.; Nilsson, R.; Nordling, C. (Phys. Status Solidi B, 1973)

(untitled) - Wagner, C. D. (Faraday Discuss. Chem. Soc., 1975)

(untitled) - Taylor, J. A. (J. Vac. Sci. Technol. (N. Y., NY, U. S.), 1982)